Modulation of 8-OH-DPAT-Induced Hypothermia by Imipramine in Rats - Yoshihisa Kitamura; Hiroaki Araki; Kazuhiko Shibata; Yutaka Gomita; Yoshiro Yoshiro (Elsevier, 2003)
ABSTRACT: The effects of imipramine on 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT), the 5-hydroxytryptamine (5-HT)1A-receptor full agonist, -induced hypothermia was examined in rats. Single administration of imipramine (30 mg/kg, i.p.) attenuated 8-OH-DPAT-induced hypothermia. This effect of imipramine was blocked by the 5-HT2A-receptor antagonist ketanserin. 8-OH-DPAT-induced hypothermia was not altered 24 h after repeated administration of imipramine (1 - 10 mg/kg per day) for 14 days. However, 8-OH-DPAT-induced hypothermia was significantly enhanced in repeated imipramine (10 mg/kg per day)-treated rats that received 8-OH-DPAT plus imipramine 24 h after the final imipramine administration for 14 days. The 5-HT2A-receptor agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane ((±)-DOI) attenuated the 8-OH-DPAT-induced hypothermia in drug naive rats. The inhibitory effect of (±)-DOI (0.3 mg/kg, s.c.) on 8-OH-DPAT-induced hypothermia was attenuated by repeated administration of imipramine (10 mg/kg per day) for 14 days. These findings suggest that enhancement of the 5-HT1A receptors by repeated administration of imipramine may be due to reduction of the inhibitory effects from the 5-HT2A receptors to the 5-HT1A receptors.